The Influence of "Si MENS" Booklet Education On Adolescent Women's Readiness For Menarche - Dina Zakiyyatul Fuadah; Nove Lestari (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2024)
Inaccuracy of information can lead to unpreparedness of young women in facing menarche. The unpreparedness of young women in facing menarche can be influenced by the knowledge of young women about menstruation that is lacking. Objective: The purpose of this study was to determine the effect of the education booklet "Si Mens" on the readiness of young women to face menarche. Methods: This study used a pre-experimental design (One Group Pretest-Posttest Design). Population 60 respondents, with purposive sampling technique obtained a sample of 38 respondents. The intervention in this study with education is to read the booklet "Si Mens" 6 times in 1 week. Data were analyzed using the Wilcoxon test. Results: The results showed that before the intervention was given, most of the respondents (76.3%) were not ready to face menarche and after the intervention, most of the respondents (63.2%) were ready to face menarche. The results of the Wilcoxon test data analysis obtained P value: 0.000 < : 0.05, which means that there is an effect of "Si Mens" booklet education on the readiness of young women to face menarche. Conclusion: Educational booklet "Si Mens" is effective for young women in dealing with menarche, with the information and knowledge so that attitudes and attitudes arise and improve youth readiness. The booklet "Si Mens" can stimulate the five senses so that it is easier for the brain to understand and generate a stimulus in the form of an attitude of readiness to face menarche.